Reconfigurable architecture model based on layered hypergraph - Fan Yang; Laixin Shen (2015 Chinese Automation Congress (CAC), 2015)
The applications of computing have led to the diversity of tasks, and one kind of architecture is difficult to adapt several different application tasks. The different requirements of computing resource, storage resource and communication resource of tasks need to be analyzed, which include the program structure running and extracting the key granularity of the real applications instinct. We can get the sub-algorithm clusters, which have independent function in different fields. Hierarchical hypergraph is used to visually describe the application structure and computing architecture, and the perception algorithm is utilized to get the system states, such as the features of applications, components state information and so on. Then the reconfigurable architecture and decision-making algorithm are utilized to achieve a reasonable matching of the sub-algorithm clusters with sub-structures. A computing instance is analyzed to verify the validity of the reconfigurable architecture. Meanwhile, the graph isomorphism theory is used to show that this diversified architecture reasonable, high-efficiency and low power consumption, while solving different complex applications.